GNG2 inhibits brain metastases from colorectal cancer via PI3K/AKT/mTOR signaling pathway - Chenhua Luo; ZhiMing Xiao; WenLong Yang (Scientific Reports)
Abstract G-protein gamma subunit 2 (GNG2) plays a vital role in various cellular processes, yet its specific function in colorectal cancer (CRC), particularly in highly invasive cases and brain metastasis, remains unclear. This study identifies GNG2 as a key regulator in metastatic colorectal cancer (mCRC) through bioinformatics analysis and experimental validation. Functional enrichment analyses reveal that GNG2 is related to the PI3K/AKT/mTOR signaling pathway and cell cycle regulation. These findings were further confirmed by in vitro and in vivo experiments. The overexpression of GNG2 significantly induced G0/G1 arrest and further inhibited the PI3K/AKT/mTOR axis in CRC cell lines, including suppressed proliferation, migration, and invasion and metastasis ability. In vivo studies using an orthotopic xenograft model demonstrated that GNG2 overexpression reduced brain metastasis and extended overall survival in mice. Immunohistochemistry and multiplex immunofluorescence confirmed the association between GNG2 overexpression, the PI3K/AKT/mTOR signaling pathway, and G0/G1 arrest. Our study suggests that GNG2 contributes to tumor suppression in CRC, particularly in preventing brain metastasis, and could serve as a promising biomarker and treatment target for mCRC, offering fresh insights into the molecular processes driving cancer progression and metastasis.